The Relationship of Various Forms of Accommodative Asthenopia with the Characteristics of the Professional Activity in Patients with Visually Intense Work and the Phenomena of Computer Visual Syndrome - I. G. Ovechkin; D. V. Gatilov; E. I. Belikova; N. I. Ovechkin; V. Kumar (Oftalʹmologiâ, 2023)
Purpose: to study the relationship of various forms of accommodative asthenopia (AA) with the characteristics of the professional activity of patients with visually stressful work (VSW) with the phenomena of computer visual syndrome (CVS).Methods. There were 150 patients with VSW — professional users of personal computers (mean age 28.8 ± 1.4 years) with myopic refraction (mean value of spherical equivalent 2.8 ± 1.1 diopters) under observation. The patients were divided into three groups: “normal” (50 patients); asthenic form of accommodative asthenopia (AFAA, pathology, 50 patients); habitual excessive tension of accommodation (HETA), pathology, 50 patients). All patients underwent a comprehensive ophthalmological examination for 13 parameters. As a basic diagnostic method, a specially developed questionnaire aimed at assessing professional activity was used. Statistical analysis of the results of the study was performed on the basis of an assessment of the average values of the correlation coefficients (ACC) between the patient’s responses (in points) and the studied indicators of the visual system.Results. High ACC were determined on issues characterizing the amount of daily visual load. However, no differences were found between APAA and HETA. The occurrence of AFAA is more often associated with the input of information, HETA — with reading. Evaluation of issues related to the regularity of the use of optical correction revealed differences in ACC (p < 0.05) between the “normal” group and the “pathology” groups, while in the “normal” group, optical correction was used in most cases “often” or “constantly”, in the “pathology” groups — “sometimes”.Conclusion. The results of the correlation assessment of the relationship between various types of AA in patients with VSW with the characteristics of professional activity and the parameters of the visual analyzer indicate the leading role of the duration and nature (input, reading of information) of daily work at a personal computer. One of the leading risk factors for the development of AA is inadequate optical correction. At the same time, there were no significant differences between AFAA and PINA. The most informative parameters of the accommodative system of the eye are the volume of absolute and relative accommodation (by the subjective method), as well as the coefficients of microfluctuations and stability of accommodogram (by the objective accommodation method).